Distinct synovial tissue macrophage subsets regulate inflammation and remission in rheumatoid arthritis - Alivernini, S; MacDonald, L; Elmesmari, A; Finlay, S; Tolusso, B; Gigante, MR; Petricca, L; Di Mario, C; Bui, L; Perniola, S; Attar, M; Gessi, M; et al. (Nature Research, 2020)
Immune-regulatory mechanisms of drug-free remission in rheumatoid arthritis (RA) are unknown. We hypothesized that synovial tissue macrophages (STM), which persist in remission, contribute to joint homeostasis. We used single-cell transcriptomics to profile 32,000 STMs and identified phenotypic changes in patients with early/active RA, treatment-refractory/active RA and RA in sustained remission. Each clinical state was characterized by different frequencies of nine discrete phenotypic clusters within four distinct STM subpopulations with diverse homeostatic, regulatory and inflammatory functions. This cellular atlas, combined with deep-phenotypic, spatial and functional analyses of synovial biopsy fluorescent activated cell sorted STMs, revealed two STM subpopulations (MerTKposTREM2high and MerTKposLYVE1pos) with unique remission transcriptomic signatures enriched in negative regulators of inflammation. These STMs were potent producers of inflammation-resolving lipid mediators and induced the repair response of synovial fibroblasts in vitro. A low proportion of MerTKpos STMs in remission was associated with increased risk of disease flare after treatment cessation. Therapeutic modulation of MerTKpos STM subpopulations could therefore be a potential treatment strategy for RA.